Association of school neighbourhood socioeconomic disadvantage and teaching staff's risk of violence at work - Ervasti, Jenni; Pentti, Jaana; Aalto, Ville; Kauppi, Maarit; Virtanen, Marianna; Kivimäki, Mika; Vahtera, Jussi (Sage, 2025)
Aim: The aim of this study was to determine the association between neighbourhood socioeconomic disadvantage and teaching staff's risk of workplace violence and whether workplace psychosocial resources can act as effect modifiers.
Methods: Primary school teaching staff in the six largest cities in Finland responded to a survey in 2018 and were linked to information on school neighbourhood disadvantage obtained from the national grid database (n = 3984).
Results: After adjustment for confounders, staff working in schools located in the most disadvantaged neighbourhoods had a 1.2-fold (95% confidence interval 1.07-1.35) risk of encountering violence or threat of violence compared with staff working in the most advantaged neighbourhoods. The association was less marked in schools with strong support from colleagues (risk ratio 1.14, 95% confidence interval (95% CI) 0.98-1.32 for high support versus 1.23, 95% CI 1.07-1.43 for low/intermediate support), a strong culture of collaboration (1.08, 95% CI 0.93-1.26 versus 1.31, 95% CI 1.12-1.53), high leadership quality (1.12, 95% CI 0.96-1.31 versus 1.29, 95% CI 1.08-1.54), and high organizational justice (1.09, 95% CI 0.91-1.32 versus 1.29, 95% CI 1.09-1.52).
Conclusions: The association between school neighbourhood and teaching staff's risk of violence was weaker in schools with high workplace psychosocial resources, suggesting that targeting these factors might help in minimizing violence at schools, but future intervention studies are needed to confirm or refute this hypothesis.